(untitled) (Zien Journal of Social Sciences and Humanities, 2022)
This article discusses the evolution of the institution of the children’s ombudsman, also analyzes the positive foreign experience, forms and methods of implementing competencies to protect the rights and interests of children, monitor the observance of children’s rights and promote their protection. Currently, a new independent institution of the Commissioner for Children’s Rights is being formed in the Republic of Uzbekistan. . The article analyzes its activities in comparison with foreign experience.